Optical polymer material, optical film, display device, method for producing optical polymer material, and method for producing optical film
By using the styrene derivatives and Malayside derivatives in the alternate convergence, the adjustment composition ratio is adjusted to reduce the elasticity coefficient and the inherent double refraction, which solves the problem of complexity and tedious design of optical polymer materials in existing technologies. , Realize the optical polymer material with low double refraction and heat resistance.
Patent Information
- Application Number
- CN202080087577.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-12-24
AI Technical Summary
The composition of the existing 5-member optical polymer materials is complex and the design is complicated, making it difficult to achieve low birefringence and low temperature dependence.
A alternative cluster formed by the lyricne derivatives and Malayside derivatives. By adjusting the composition ratio of the styrene derivatives, the light elastic coefficient and the inherent double refraction are reduced to achieve low dual -refractive characteristics.
A low-birefringence optical polymer material with simple composition and easy design has been realized. It has excellent low-birefringence properties and heat resistance and is suitable for optical films in display devices.
Smart Images

Figure CN114846372B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical polymer material, an optical film, a display device, a method for producing the optical polymer material, and a method for producing the optical film. Background Art
[0002] In recent years, display devices represented by liquid crystal display devices (LCD) and organic light emitting diode (OLED) display devices have been used as display devices for various devices. For example, these display devices are used in computer display devices, television receivers, instrument panels mounted on automobiles, airplanes, ships, etc., navigation devices, portable information terminal devices such as smartphones, or digital signage (electronic signs) used for advertising and guidance displays.
[0003] A variety of optical polymer films are used in these display devices, which helps to achieve excellent image quality. Among them, for example, the polarizing plate protective film is expected to suppress the birefringence to a very small level. In addition, low birefringence is also required in polymers used for pickup lenses and LCD backlights. In order to suppress the birefringence to a small level, it is preferred that the intrinsic birefringence and photoelastic birefringence are small. In addition, if the use under a wide range of ambient temperatures is considered, it is preferred that the temperature dependence of the intrinsic birefringence is low (for example, non-patent document 1). In order to achieve such an optical polymer material with low temperature dependence and low birefringence, 4-component and 5-component optical polymer materials have been required in the past.
[0004] Prior art literature
[0005] Non-patent literature
[0006] Non-patent document 1: MD Shikanai, A. Tagaya and Y. Koike, Appl. Phys. Lett., 108 pp. 131902 (2016). Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, pentad-based optical polymer materials have complex compositions and require complicated designs for obtaining desired properties, thus presenting practical problems.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a low-birefringence optical polymer material, an optical film, a method for producing the same, and a display device using the same, which has a simple composition and is easy to design to obtain desired characteristics.
[0010] Means for solving problems
[0011] In order to solve the above-mentioned problems and achieve the purpose, an optical polymer material according to one embodiment of the present invention is characterized in that it comprises an alternating copolymer formed by monomers of a styrene derivative and monomers of a maleimide derivative, and the photoelastic coefficient has a nonlinear characteristic that it decreases to a first value as the composition ratio of the styrene derivative increases, and increases compared to the first value if the composition ratio of the styrene derivative further increases. The styrene derivative is within a specified composition ratio range, and within the composition ratio range, the absolute value of the photoelastic coefficient is less than a first absolute value, and the absolute value of the intrinsic birefringence is less than a second absolute value.
[0012] An optical polymer material according to one embodiment of the present invention is characterized in that it includes a polymer formed from a monomer of a styrene derivative, a monomer of a maleimide derivative, and a monomer of a modified organic compound, wherein the modified organic compound has different physical property values related to mechanical strength from the monomer of the styrene derivative and the monomer of the maleimide derivative, and in the relationship between the monomer of the styrene derivative and the monomer of the maleimide derivative, the photoelastic coefficient has a nonlinear characteristic that decreases to a second value as the composition ratio of the styrene derivative increases and increases compared to the second value if the composition ratio of the styrene derivative further increases, and the styrene derivative has an absolute value of the photoelastic coefficient of the styrene derivative within a prescribed composition ratio range and is less than a third absolute value within the composition ratio range, and an absolute value of the intrinsic birefringence is less than a fourth absolute value.
[0013] An optical film according to one embodiment of the present invention includes the optical polymer material.
[0014] A display device according to one embodiment of the present invention includes the optical film.
[0015] A method for manufacturing an optical polymer material according to one embodiment of the present invention is characterized in that it includes a step of forming an optical polymer material, wherein the optical polymer material includes an alternating copolymer formed by monomers of a styrene derivative and monomers of a maleimide derivative, and wherein the styrene derivative is within a specified composition ratio range to form an optical polymer material in which the absolute value of the photoelastic coefficient is less than a first absolute value and the absolute value of the intrinsic birefringence is less than a second absolute value.
[0016] A method for producing an optical polymer material according to one embodiment of the present invention is characterized in that it includes a step of forming an optical polymer material, wherein the optical polymer material includes a polymer formed from a monomer of a styrene derivative, a monomer of a maleimide derivative and a monomer of a modified organic compound, wherein the modified organic compound has physical property values related to mechanical strength different from those of the monomer of the styrene derivative and the monomer of the maleimide derivative, and wherein the styrene derivative is within a specified composition ratio range, and the optical polymer material is formed such that the absolute value of the photoelastic coefficient is less than the third absolute value and the absolute value of the intrinsic birefringence is less than the fourth absolute value within the range of the composition ratio.
[0017] A method for producing an optical film according to one embodiment of the present invention is characterized in that the optical film is produced by thinning the optical polymer material produced by the production method.
[0018] Effects of the Invention
[0019] According to the present invention, it is possible to realize an optical polymer material and an optical film having a simple composition and easy design such as a binary or ternary system and having extremely preferable low birefringence characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic exploded perspective view of a main part of a liquid crystal display device using an optical film formed of the optical polymer material according to the embodiment.
[0021] Figure 2 This is a graph showing the relationship between the intrinsic birefringence and the mass ratio of styrene in an optical polymer film containing P(St / EMI).
[0022] Figure 3 This is a graph showing the relationship between the photoelastic coefficient and the mass ratio of styrene in an optical polymer including P(St / EMI).
[0023] Figure 4 This is a graph showing the relationship between the temperature coefficient of intrinsic birefringence and the mass ratio of styrene in an optical polymer film containing P(St / EMI).
[0024] Figure 5 This is a diagram showing the relationship between the ratio of the monomer M1 in the alternating polymer and the ratio of the monomer M1 in the blended monomer.
[0025] Figure 6 It is a graph showing the relationship between the molar ratio of the monomer M1 and the polymerization rate.
[0026] Figure 7 It is a bar graph showing the composition distribution when the conversion rate is set to 80%.
[0027] Figure 8 This is a graph showing the relationship between the photoelastic coefficient and the mass ratio of styrene in optical polymer materials having different maleimide derivatives.
[0028] Fig. 9 This is a graph showing the relationship between the intrinsic birefringence and the mass ratio of styrene in an optical polymer film containing P(St / MMA).
[0029] Fig.10 This is a graph showing the relationship between the photoelastic coefficient and the mass ratio of styrene in an optical polymer including P(St / MMA).
[0030] Fig.11 It is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / MMA).
[0031] Fig.12 It is a diagram showing a two-dimensional birefringence diagram of P(St / CHMI / MMA).
[0032] Fig.13 It is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / TCEMA).
[0033] Fig.14 It is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / tBuMI). DETAILED DESCRIPTION
[0034] Hereinafter, an embodiment of the present invention will be described in detail with reference to the accompanying drawings. In addition, the present invention is not limited to the embodiment. In addition, in each of the accompanying drawings, the same or corresponding elements are appropriately marked with the same reference numerals. In addition, it should be noted that the accompanying drawings are schematic, and the relationship between the dimensions of the elements is sometimes different from the actual. The drawings sometimes also include parts with different dimensional relationships and ratios.
[0035] The optical polymer material according to the embodiment of the present invention is used as a material for an optical film in a liquid crystal display device, for example. Figure 1 This is a schematic exploded perspective view of the main parts of a liquid crystal display device using an optical film formed of an optical polymer material according to an embodiment. The liquid crystal display device 10 has a known structure in which a backlight 1, a polarizing plate 2, a phase difference film 3, a glass substrate with a transparent electrode 4, a liquid crystal layer 5, a glass substrate with a transparent electrode 6, an RGB color filter 7, a phase difference film 8, and a polarizing plate 9 are sequentially stacked.
[0036] In the liquid crystal display device 10 , the optical film formed of the optical polymer material of the embodiment can be suitably used as the retardation films 3 and 8 and the protective films attached to both surfaces of the polarizing plates 2 and 9 .
[0037] The optical polymer material of the embodiment of the present invention includes an alternating copolymer formed of a monomer of a styrene derivative and a monomer of a maleimide derivative. According to the in-depth study of the present inventors, the birefringence characteristics of the optical polymer material including the alternating copolymer formed of a monomer of a styrene derivative and a monomer of a maleimide derivative change nonlinearly according to the composition ratio of the styrene derivatives contained therein. This nonlinear change in the birefringence characteristics is a nonlinear characteristic in which the photoelastic coefficient decreases to a certain specified value as the composition ratio of the styrene derivative increases, and then if the composition ratio of the styrene derivative is further increased, the photoelastic coefficient rises to a value higher than the specified value.
[0038] Therefore, the present inventors have found an optical polymer material which has a simple composition and easy design like a binary system and has extremely preferable low birefringence characteristics by utilizing this nonlinearity. Specifically, the present inventors have found that a styrene derivative can achieve characteristics such that the absolute value of the photoelastic coefficient is less than a first value which is relatively small, and the absolute value of the intrinsic birefringence is less than a second value which is relatively small, within a predetermined composition ratio range.
[0039] For optical films used in display devices such as liquid crystal display devices and optical devices, stress is usually applied during use, so photoelastic birefringence (also called stress birefringence) is generated. Photoelastic birefringence is proportional to the photoelastic coefficient and stress, so if the photoelastic coefficient is small, the photoelastic birefringence also becomes small. Therefore, if the absolute values of the photoelastic coefficient and the intrinsic birefringence are small, extremely preferred low birefringence characteristics can be achieved. In addition, the photoelastic coefficient and the intrinsic birefringence are quantities inherent to the substance.
[0040] If the first absolute value, which is the upper limit of the absolute value of the photoelastic coefficient, is 50×10 -12 Pa -1 is small enough, but preferably 10×10 -12 Pa -1 , more preferably 2×10 -12 Pa -1 In addition, if the second absolute value, which is the upper limit of the absolute value of the intrinsic birefringence, is 20×10 -3 is small enough, but preferably 5×10 -3 , more preferably 1×10 -3 .
[0041] In addition, if the absolute value of the temperature coefficient of intrinsic birefringence is 2×10 -5 ℃ -1 Less than, more preferably 1×10 -5 ℃ -1 Below this value, the temperature dependence of birefringence is small, and thus suitable birefringence characteristics can be maintained in a wide range of environmental temperatures.
[0042] It should be noted that, in optical polymer materials containing random polymers, the intrinsic birefringence, photoelastic coefficient, and temperature coefficient of intrinsic birefringence usually change linearly with respect to the composition ratio of the monomers. However, in the optical polymer materials of the embodiments of the present invention, the birefringence characteristics change nonlinearly depending on the composition ratio of the styrene derivatives. Therefore, it is believed that suitable birefringence characteristics can be achieved with a simple composition such as a binary system and in an easily designed manner.
[0043] Furthermore, the present inventors have found that the optical polymer material according to the embodiment of the present invention has extremely excellent flexibility and heat resistance compared to conventional low-birefringence optical polymer materials.
[0044] Here, maleimide has a five-membered ring formed by imidization of maleic acid as a basic structure, and the hydrogen atom bonded to the nitrogen atom is substituted by various substituents, thereby constituting various maleimide derivatives. In addition, styrene has a structure in which one of the hydrogen atoms of benzene is substituted by a vinyl group as a basic structure, and the hydrogen atom is substituted by various substituents, thereby constituting various styrene derivatives.
[0045] The structural formula of N-ethylmaleimide is shown below. The molecular weight of N-ethylmaleimide is 125.13.
[0046]
Chemical formula 1
[0047]
[0048] The structural formula of styrene is shown below: The molecular weight of styrene is 104.15.
[0049]
Chemical formula 2
[0050]
[0051] In addition, an example of the structural formula of an alternating copolymer composed of N-ethylmaleimide and styrene is shown below.
[0052]
Chemical formula 3
[0053]
[0054] In addition, the maleimide derivative is represented by the following general formula, for example.
[0055]
Chemical formula 4
[0056]
[0057] (R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, 1-methylpropyl, 2-methylpropyl, pentyl, cyclopentyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, 1-ethylpropyl, 2-ethylpropyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, hexyl, cyclohexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1-ethylbutyl, 2-ethylbutyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 1,1,2-trimethylpropyl, 1,2,2-trimethylpropyl, 1-methyl-1-ethylpropyl, 1-ethyl- 2-methylpropyl, 1,1-diethylethyl, 2-ethylhexyl, dodecyl, lauryl, hydroxymethyl, 2-hydroxyethyl, chloromethyl, dichloromethyl, trichloromethyl, fluoromethyl, difluoromethyl, trifluoromethyl, chlorofluoromethyl, dichlorofluoromethyl, bromomethyl, iodomethyl, 1-chloroethyl, 2-chloroethyl, 2,2,2-trichloroethyl, 1,1,2,2,2-pentachloroethyl, 1-fluoroethyl, 2-fluoroethyl, 2,2,2-trifluoromethyl, 1,1,2,2,2-pentafluoroethyl, 2-bromoethyl, 2,2,2-tribromoethyl, etc. X1 and X2 may be the same or different and may be selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, methyl, etc. Among them, R, X1, and X2 are not limited to these. For example, R may be phenyl or benzyl. )
[0058] In addition, the styrene derivative is represented by the following general formula, for example.
[0059]
Chemical formula 5
[0060]
[0061] (X1 to X3 may be the same or different and are selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, methyl, etc. Y1 to Y5 may be the same or different and are selected from hydrogen, fluorine, chlorine, bromine, iodine, hydroxyl, methyl, hydroxymethyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, hexyl, etc. However, X1 to X3 and Y1 to Y5 are not limited to these.)
[0062] The maleimide derivative and the styrene derivative represented by these general formulas correspond to the structures of monomers observed in monomer units that finally form a polymer in the optical polymer material according to the embodiment of the present invention.
[0063] It should be noted that in the polymerization reaction of the maleimide derivative and the styrene derivative, the monomer reactivity ratios r1 and r2 are extremely small, and an alternating copolymer is easily formed.
[0064] Hereinafter, an alternating copolymer formed of a monomer of a styrene derivative and a monomer of a maleimide derivative may be described as a St / XMI polymer or P(St / XMI). XMI is described as EMI when the maleimide derivative is, for example, N-ethylmaleimide. It is described as MeMI when N-methylmaleimide. It is described as CHMI when N-cyclohexylmaleimide. It is described as tBuMI when N-tert-butylmaleimide. In addition, below, St is styrene represented by the chemical formula C6H5CH=CH2 unless otherwise specified.
[0065] (Sample production)
[0066] Samples are prepared to confirm the characteristics of the optical polymer material of the embodiment of the present invention. It should be noted that, as a method for synthesizing an alternating copolymer formed by a styrene derivative and a maleimide derivative, there is also a method as follows: the material that will become a maleimide derivative is alternately copolymerized with the material that will become a styrene derivative, and then the side chain is reacted to synthesize an alternating copolymer formed by a maleimide derivative and a styrene derivative. The material that becomes a maleimide derivative refers to a material that can become a maleimide derivative as a monomer unit through side chain reactions, etc. after being incorporated into the alternating copolymer. Similarly, the material that becomes a styrene derivative refers to a material that can become a styrene derivative as a monomer unit through side chain reactions, etc. after being incorporated into the alternating copolymer. As a material that becomes a maleimide derivative, there are, for example, maleic anhydride derivatives or maleic acid derivatives. In addition, the alternating copolymer synthesized in this way can also be reacted with any side chain to produce a polymer with a desired structure.
[0067] Here, an alternating copolymer was prepared using XMI and St. First, St, EMI, MeMI, tBuMI, and CHMI manufactured by Tokyo Chemical Industry Co., Ltd. were prepared as reagents. St was purified by vacuum distillation. In addition, methanol and dichloromethane manufactured by Wako Pure Chemical Industries, Ltd. were prepared as solvents.
[0068] Then, polymerization was carried out through the following steps.
[0069] 1. Add XMI (EMI, MeMI, tBuMI or CHMI) and St monomers, a polymerization initiator, and a chain transfer agent into a test tube for mixing. It should be noted that the mixing ratio of XMI to St can be various values. For example, the monomer added is set to 100% XMI or 100% St.
[0070] 2. After sealing the test tube, mix the contents by sufficient shaking, and perform ultrasonic degassing and dispersion.
[0071] 3. Place the test tube in a hot water bath at 70°C for 24 hours to allow polymerization to proceed.
[0072] The bulk obtained by cutting off both ends of the cylindrical bulk of the optical polymer material produced by the above steps is further purified by the following steps.
[0073] 1. The block was broken into pieces of about 1 cm square and placed in dichloromethane to prepare a uniform polymer solution.
[0074] 2. The polymer solution was added dropwise to methanol to precipitate the polymer.
[0075] 3. Filter with filter paper, recover the polymer remaining on the filter paper, dry under reduced pressure in a desiccator for about 2 to 3 hours, and then further dry under reduced pressure in a 105°C reduced pressure dryer for more than 24 hours.
[0076] The glass transition temperature of the purified polymer obtained through the above steps was measured using a differential scanning calorimeter DSC-60 (DSC) manufactured by Shimadzu Corporation.
[0077] Furthermore, the purified polymer is formed into a thin film by the following steps.
[0078] 1. Add 8-20 g of dichloromethane to 1-2 g of the purified polymer to prepare a uniform polymer solution.
[0079] 2. In a fume hood, use an applicator to spread the polymer solution on the release PET film.
[0080] 3. Cover the developed polymer solution with a lid and evaporate the solvent slowly.
[0081] 4. The polymer film formed on the PET film was peeled off and dried under reduced pressure in a reduced pressure dryer for more than 24 hours. For polymer films with a glass transition temperature of 125°C or less, the reduced pressure drying was performed at 90°C, and for other polymer films, the reduced pressure drying was performed at 105°C.
[0082] The photoelastic coefficient of the produced polymer film was measured using the automatic birefringence control device ABR-EX manufactured by Uniopt. It should be noted that the measurement of the photoelastic coefficient is carried out as follows. First, a stress of 0 to 2N is applied at intervals of about 0.1N to a sample film with a measurement portion of the film set to a width of 4 to 5mm and a thickness of about 35 to 55μm, and the delay amount is measured. Then, the photoelastic coefficient is calculated from the delay amount in the range of about 0.3 to 2N and the width of the measurement portion. Therefore, the maximum applied stress when measuring the photoelastic coefficient is about 2N.
[0083] Next, the polymer film produced was subjected to uniaxial heat stretching using a film-making biaxial stretching device, i.e., IMC-C513, of a well-made institute. Then, the internal stress was relaxed by standing for more than 24 hours, and the orientation of the stretched film was evaluated using infrared dichroism according to the absorbance in the infrared region of the Fourier transform infrared spectrophotometer and Varian 7000e made by Varian. In addition, the automatic birefringence control device ABR-10A made by Uniopt was used to measure the retardation of the stretched film. Then, the intrinsic birefringence was calculated by the retardation, orientation, and thickness of the film. In addition, the refractive index was measured for a portion of the polymer film to estimate the copolymerization composition ratio.
[0084] When the film thickness is d, the retardation is Re, and the orientation birefringence is Δn or , set the intrinsic birefringence to Δn 0 , when the orientation degree is set to f, the following relationship holds.
[0085] Re=Δn or ·d=Δn 0 ·f·d
[0086] Therefore, the intrinsic birefringence can be calculated from the retardation, the degree of orientation, and the thickness of the film.
[0087] Examples of the measurement results are shown in Table 1. The intrinsic birefringence calculated from the measurement results can be defined as a value calculated as an average of the entire polymer by weighting the intrinsic birefringence of each component polymer by the weight fraction of each component polymer.
[0088]
Table 1
[0089]
[0090] (Birefringence characteristics)
[0091] The birefringence characteristics of the optical polymer film produced as described above will be described. First, the birefringence characteristics of the optical polymer film including P(St / EMI) produced by blending a larger amount of EMI monomer than St monomer will be described. Figure 2 This is a graph showing the mass ratio of intrinsic birefringence to styrene in an optical polymer film at 25°C. The vertical axis represents intrinsic birefringence Δn 0. The horizontal axis expresses the composition ratio of St in the optical polymer film as a mass ratio in percentage (wt.%). It should be noted that St is considered to exist in the optical polymer film in the form of an alternating copolymer or a homopolymer. The mass ratio refers to the ratio of the sum of the mass of St constituting the alternating copolymer and the mass of St constituting the homopolymer to the mass of the optical polymer film. That is, the data point with a mass ratio of 0% is the data of the optical polymer film produced using only EMI without using St. And, the data point with a mass ratio of 100% is the data of the optical polymer film produced using only St without using XMI. It should be noted that the mass ratio of St is calculated from the refractive index measured at a wavelength of 594nm, assuming that the refractive index changes linearly with respect to the mass ratio. As Figure 2 As shown in FIG. 1 , it was confirmed that the intrinsic refractive index changes linearly with respect to the mass ratio of St.
[0092] Figure 3 This is a graph showing the relationship between the photoelastic coefficient and the mass ratio of styrene in an optical polymer. The horizontal axis represents the composition ratio of St in the optical polymer film as a mass ratio in percentage (wt.%). The vertical axis represents the photoelastic coefficient C. It should be noted that the mass ratio of St is calculated from the refractive index measured at a wavelength of 594 nm, assuming that the refractive index changes linearly with respect to the mass ratio.
[0093] like Figure 3 As shown in FIG. 1 , it was confirmed that the change in the photoelastic coefficient with respect to the mass ratio of St deviated significantly from the linearity. Specifically, it was confirmed that the photoelastic coefficient decreased to -2×10 -12 Pa -1 If the composition ratio is further increased, it will rise and change to -2×10 -12 Pa -1 Compared to the rising nonlinear shape, that is, convex or V-shaped. However, it should be noted that Figure 3 The value confirmed in is -2×10 -12 Pa -1 It does not necessarily coincide with the minimum value of the V-shape.
[0094] Figure 4 This is a graph showing the relationship between the temperature coefficient of intrinsic birefringence in an optical polymer film and the mass ratio of styrene. The horizontal axis represents the composition ratio of St in the optical polymer film as a mass ratio in percentage (wt.%). The vertical axis represents the temperature coefficient of intrinsic birefringence (dΔn 0 / dT). It should be noted that the mass ratio of St is calculated from the refractive index measured at a wavelength of 594 nm, assuming that the refractive index changes linearly with respect to the mass ratio.
[0095] like Figure 4As shown in FIG. 1 , it was confirmed that the temperature coefficient of intrinsic birefringence deviated greatly from the linearity with respect to the change of the mass ratio of St. Specifically, it was confirmed that the temperature coefficient changed in an upward convex or inverted V shape. In addition, the temperature coefficient was 1.2×10 -5 ℃ -1 The following is confirmed to satisfy 2×10 -5 ℃ -1 It should be noted that Figure 3 Similarly, the confirmed value of 1.2×10 -5 ℃ -1 It is not limited to the maximum value of the V-shape, but it is definitely greater than 2×10 -5 ℃ -1 Largely small value.
[0096] An example of the properties of the produced optical polymer material and optical film is shown in Table 2. Tg is the glass transition temperature. St (wt.%) and EMI (wt.%) are the mass ratios at the time of compounding, i.e., at the time of feeding (in feed). As shown in Table 2, when St is 23.3wt.% and EMI is 76.7wt.%, an extremely high glass transition temperature of 193.9°C is obtained, confirming that the heat resistance is extremely high. In addition, the intrinsic birefringence Δn 0 0.07×10 at 25°C -3 , temperature coefficient dΔn 0 / dT is 0.72×10 -5 ℃ -1 , the photoelastic coefficient C is 0.91×10 -12 Pa -1 , are all extremely low values close to zero, confirming good low birefringence characteristics.
[0097]
Table 2
[0098] (Table 2)
[0099]
[0100] Next, for the samples in Table 2, proton nuclear magnetic resonance ( 1 H-NMR) to determine the composition ratio of the copolymer (Incopolymer). Figure 2 The results shown are calculated for Δn 0 The composition ratio is zero (calculated as Δn 0=0) and the composition ratio in feed ((in feed)) are shown in Table 3. As shown in Table 3, it was confirmed that good low birefringence characteristics can be achieved in P(St / EMI=31 / 69(wt.%)). It should be noted that, for such optical polymer materials and optical films, it was also confirmed that the characteristics were achieved when St was 23.3wt.% and EMI was 76.7wt.% in the feed composition. In addition, P(St / EMI=31 / 69(wt.%)) is expressed as P(St / EMI=35 / 65(mol%)) when expressed as a molar ratio. In addition, the difference between the calculated composition ratio and the actual composition ratio is within 1%. This suggests that in the polymer system containing P(St / EMI) (P(St / EMI) system), there is an extremely high linearity between the intrinsic birefringence and the composition ratio. It should be noted that the composition most suitable for reducing birefringence varies depending on the structure of each monomer. For example, the present inventors have predicted through calculation that in the P(St / CHMI) system, the birefringence becomes particularly small at a composition near (St / CHMI=16 / 84 (wt.%)). That is, it is predicted that within the specified range including (St / CHMI=16 / 84 (wt.%)), the absolute value of the photoelastic coefficient can be 50×10 -12 Pa -1 The absolute value of intrinsic birefringence is 20×10 -3 The following are the preferred characteristics.
[0101]
Table 3
[0102] (Table 3)
[0103] ratio St (wt.%) EMI(wt.%) <![CDATA[Δn 0 =0 is the composition ratio of zero]]> 30.6 69.4 Composition ratio of feed 23.3 76.7 Composition ratio in copolymer 31 69
[0104] (Copolymer composition analysis based on Mayo-Lewis formula)
[0105] Next, for the P(St / EMI) system, the copolymer composition is analyzed based on the Mayo-Lewis formula (for example, refer to I. Skeist, J. Am. Chem. Soc., 68, p. 1781 (1946), M. Fineman, SD Ross, J. Polym. Sci., 5, 2, p. 259-265 (1949), R. Kitamura, kobunshi, 14, 160, p. 564-573 (1965) etc.).
[0106] When the monomer M1 and the monomer M2 are St and EMI, respectively, the monomer reactivity ratios r1 and r2 are 0.05 and 0.01. In addition, when the monomer M1 and the monomer M2 are St and CHMI, respectively, the monomer reactivity ratios r1 and r2 are extremely small, 0.13 and 0.0053 (for example, refer to H. Aida, I. Takase, M. Kobayashi, Fukui University Engineering Research Report, 31, 1, p. 43-50 (1985), T. Oishi, M. Fujimoto, and Y. Haruta, Kobunshi Ronbunshu, 48 (3), p. 123-128 (1991)). Therefore, the monomer M1 and the monomer M2 are set to St and EMI, respectively, and the copolymer composition is analyzed.
[0107]
Table 4
[0108] (Table 4)
[0109] <![CDATA[M1]]> <![CDATA[M2]]> <![CDATA[r1]]> <![CDATA[r2]]> St EMI 0.05 0.01 St CHMI 0.13 0.053
[0110] Figure 5 It is a graph showing the relationship between the ratio of M1 in the polymer and the ratio of M1 (St) in the monomers to be matched. In the horizontal axis, for example, 0 means that all the monomers to be matched are M2 (EMI), and 1 means that all the monomers to be matched are M1. In addition, the vertical axis shows the ratio of M1 in the polymer instantly generated under the ratio of the horizontal axis.
[0111] like Figure 5 As shown in FIG. 1 , as long as the ratio of M1 increases slightly from 0, the ratio of M1 in the polymer rapidly reaches 0.5. Then, it is maintained at 0.5 until the ratio of M1 is very close to 1. This indicates that alternating copolymers of M1 and M2 are easily generated. It should be noted that such a trend is confirmed to not change significantly even when r1 and r2 are changed in the range of about 0.01 to 0.1.
[0112] Figure 6 This is a graph showing the relationship between the molar ratio of M1 and the polymerization rate when M1 and M2 are St and EMI, respectively. The polymerization rate is the ratio of the monomers that become polymers among all the monomers blended to produce a polymer material.
[0113] Figure 6Here, the monomer composition refers to the molar ratio of the monomer of M1, which is about 23% when the polymerization rate P is 0%, and 0% when the polymerization rate P is about 50%. This means that all the monomers of M1 become polymers. In addition, the instantaneous copolymer composition refers to the molar ratio of the polymer instantly generated at its polymerization rate P, and is 50% even when the polymerization rate P is 0%. This means that alternating copolymers are generated from the initial stage of the polymerization. In addition, it drops sharply to 0% near the polymerization rate P of 50%. This is because the monomer of M1 used to generate the alternating copolymer is 0%. In addition, the accumulated copolymer composition refers to the cumulative value of the polymer containing M1. Alternating copolymers are generated from the polymerization rate P from 0% to about 50%, so it is about 50%, but when it is above 50%, the generation of homopolymers of M2 proceeds, so the relative proportion of the polymer containing M1 (roughly alternating copolymers) is relatively reduced. It should be noted that due to Figure 6 Since it is a calculated value, the polymerization rate P is shown to be 100%, but in reality, as the polymerization reaction proceeds, the monomer becomes difficult to move in the polymer, so if a certain degree of polymerization rate is reached, the polymerization reaction decreases. In addition, it was confirmed that such a trend does not change significantly even when r1 and r2 are changed in the range of about 0.01 to 0.1.
[0114] Here, in the produced optical polymer material and optical film, P (St / EMI=35 / 65 (mol%)) was present, and thus it was suggested that the conversion rate to the polymer was about 80%.
[0115] Figure 7 It is a bar graph showing the composition distribution when the conversion rate is set to 80%. Figure 7 It indicates the following. That is, the polymer with very high alternating copolymerization, including 40-50% of M1 (St), accounts for about 55% of the whole, the polymer containing 5% or less of M1 which is a homopolymer of approximately M2 (EMI), accounts for about 35% of the whole, and the remaining about 10% is a polymer of a composition in between. Among them, the polymer containing 40-50% of M1 is an alternating copolymer of M1 and M2, that is, P (St-alt-EMI), because r1 and r2 << 1.
[0116] (Photoelastic coefficient of various P(St / XMI))
[0117] Next, the measurement results of the photoelastic coefficients of maleimide derivatives with different P(St / XMI) will be described. Figure 8It is a graph showing the photoelastic coefficient of P (St / XMI) when XMI is EMI, CHMI, MeMI, and tBuMI. It should be noted that in any case, the mass ratio of St is calculated from the refractive index measured at a wavelength of 594nm, assuming that the refractive index changes linearly with respect to the mass ratio. In addition, when the horizontal axis is 100wt.%, the data points of the four types of P (St / XMI) roughly overlap. In any case, it is confirmed that the photoelastic coefficient has a nonlinear characteristic that decreases with the increase of the mass ratio of St and increases with the further increase of the mass ratio of St. The reason for such nonlinearity may not be clear, but it is expected to be the interaction between the skeleton of the maleimide derivative and the benzene ring of the St derivative.
[0118] (Haze value of the blended polymer of P(St / EMI) and PEMI)
[0119] Next, P (St / EMI = 30 / 70 (wt.%)) and a homopolymer of EMI (PEMI) were mixed in equal amounts, dissolved in dichloromethane, and developed on a peeled PET film in the same manner as described above to prepare a film-forming polymer blend. The glass transition temperature and haze value of the polymer blend were then measured. As a result, although it was a polymer blend, the haze value was 1.26%, which was equivalent to the haze value of polymethyl methacrylate (PMMA), i.e., 1.25%.
[0120] In addition, the glass transition temperature of the polymer blend is 220. This is a value equivalent to the glass transition temperature of P (St / EMI = 30 / 70 (wt.%)) which is 185 and the glass transition temperature of PEMI which is 257°C which is an average value of 221. In addition, the glass transition endothermic peak of the polymer blend is one. This suggests that the polymer blend has high compatibility. In addition, the low haze value also suggests high compatibility.
[0121] On the other hand, when producing P(St / EMI) polymers, it is confirmed that when the amount of St input is large, turbidity sometimes occurs. Therefore, in order to reduce the haze value, when producing optical polymer materials, it is preferred to mix more monomers of maleimide derivatives (or materials that become maleimide derivatives) than monomers of styrene derivatives (or materials that become styrene derivatives). Alternatively, it is also possible to use a polymer blending method to produce.
[0122] (Other Embodiments)
[0123] The present inventors studied the inclusion of a monomer of a methacrylic acid derivative as a modified organic compound in the constituent materials of the polymer in addition to a styrene derivative and a maleimide derivative in order to modify the optical polymer material of the embodiment. The styrene derivative and the maleimide derivative have, for example, positive photoelastic coefficients, but the methacrylic acid derivative has different physical property values related to mechanical strength, such as glass transition temperature, compared to the monomers of the styrene derivative and the maleimide derivative, and has, for example, a negative photoelastic coefficient.
[0124] As a result, the present inventors have discovered an optical polymer material comprising a polymer formed of a monomer of a styrene derivative, a monomer of a maleimide derivative, and a monomer of a methacrylic acid derivative, and the photoelastic coefficient has the following nonlinear characteristics, that is, in the relationship between the monomer of the styrene derivative and the monomer of the maleimide derivative, the photoelastic coefficient decreases to a second value as the composition ratio of the styrene derivative increases, and when the composition ratio of the styrene derivative further increases, the photoelastic coefficient exceeds the second value, and for the optical polymer material, the styrene derivative is within a prescribed composition ratio range, and within the composition ratio range, the absolute value of the photoelastic coefficient is less than or equal to the third absolute value, and the absolute value of the intrinsic birefringence is less than or equal to the fourth absolute value. The third absolute value is, for example, 50×10 -12 Pa -1 , the fourth absolute value is, for example, 20×10 -3 In addition, the inventors of the present invention have come up with the idea that in the optical polymer material, the composition ratio of the styrene derivative and the composition ratio of the maleimide derivative are set in such a manner that the coordinate points indicated by the first photoelastic coefficient and the first intrinsic birefringence determined by the composition ratio of the styrene derivative and the composition ratio of the maleimide derivative and the coordinate points indicated by the second photoelastic coefficient and the second intrinsic birefringence of the methacrylic acid derivative are located at positions sandwiching the origin, and the composition ratio of the methacrylic acid derivative is set in such a manner that the first photoelastic coefficient and the first intrinsic birefringence are offset, thereby realizing an optical polymer material having a simple composition such as a ternary system, easy design, extremely preferred low birefringence characteristics, and improved characteristics with respect to mechanical strength.
[0125] Furthermore, the present inventors have found that, in an optical polymer material including a polymer formed from a monomer of a styrene derivative, a monomer of a maleimide derivative, and a monomer of a methacrylic acid derivative, in a two-dimensional birefringence diagram defined by a photoelastic coefficient and an intrinsic birefringence, by setting the composition ratio of any two of the styrene derivative, the maleimide derivative, and the methacrylic acid derivative so that the coordinate points indicated by the first photoelastic coefficient and the first intrinsic birefringence and the coordinate points indicated by the second photoelastic coefficient and the second intrinsic birefringence of the other of the styrene derivative, the maleimide derivative, and the methacrylic acid derivative are located at positions sandwiching the origin, and by setting the composition ratio of the other so that the first photoelastic coefficient and the first intrinsic birefringence are offset, an optical polymer material having a simple composition such as a ternary system, easy design, extremely preferred low birefringence characteristics, and improved characteristics with respect to mechanical strength can be realized.
[0126] In the above study, the inventors first prepared a copolymer using St and a methacrylic acid derivative as a preliminary study. MMA (methyl methacrylate) was used as a methacrylic acid derivative. First, MMA manufactured by Wako Pure Chemical Industries, Ltd. was prepared as a reagent. MMA was purified by vacuum distillation. In addition, methanol and dichloromethane manufactured by Wako Pure Chemical Industries, Ltd. were prepared as solvents.
[0127] Then, polymerization is carried out by a process similar to the case of the alternating copolymer but with the conditions appropriately optimized. The block obtained by cutting off both ends of the cylindrical block of the optical polymer material produced by this process is further purified by a process similar to the case of the alternating copolymer but with the conditions appropriately optimized.
[0128] The glass transition temperature of the purified polymer obtained through the above process was measured using DSC-60 (DSC).
[0129] Furthermore, the purified polymer is formed into a thin film by the same process as in the case of the alternating copolymer but with the conditions appropriately optimized.
[0130] The photoelastic coefficient of the produced polymer film was measured using ABR-EX.
[0131] Next, the polymer film was subjected to uniaxial heat stretching using the IMC-11A9 biaxial stretching device of the Well Moto Seisakusho. Then, the internal stress was relaxed by standing for more than 24 hours, and the orientation of the stretched film was evaluated using infrared dichroism based on the absorbance in the infrared region of Varian 7000e. In addition, the retardation of the stretched film was measured using ABR-10A. Then, the intrinsic birefringence was calculated based on the retardation, orientation and thickness of the film. In addition, the refractive index of a portion of the polymer film was measured to infer the copolymer composition ratio.
[0132] Fig. 9 This is a graph showing the relationship between the intrinsic birefringence of an optical polymer film containing P (St / MMA) at 25°C and the mass ratio of styrene. The vertical axis represents the intrinsic birefringence Δn 0 The horizontal axis represents the composition ratio of St in the optical polymer film as a mass ratio in percentage (wt.%). It should be noted that the mass ratio of St is calculated from the refractive index measured at a wavelength of 594 nm, assuming that the refractive index changes linearly with respect to the mass ratio. Fig. 9 As shown in FIG. 1 , it was confirmed that the intrinsic refractive index changes linearly with respect to the mass ratio of St.
[0133] Fig.10 This is a graph showing the relationship between the photoelastic coefficient and the mass ratio of styrene in an optical polymer including P (St / MMA). The horizontal axis represents the composition ratio of St in the optical polymer film as a mass ratio in percentage (wt.%). The vertical axis represents the photoelastic coefficient C. It should be noted that the mass ratio of St is calculated from the refractive index measured at a wavelength of 594 nm, assuming that the refractive index changes linearly with respect to the mass ratio.
[0134] like Fig.10 As shown, it was confirmed that the change in the photoelastic coefficient with respect to the mass ratio of St deviated greatly from the linearity and changed convexly. In addition, it was confirmed that the photoelastic coefficient of the optical polymer was negative when the mass ratio of St was 0%, that is, when MMA was 100%.
[0135] Using the above results of P(St / MMA) and P(St / EMI), a two-dimensional birefringence diagram of a ternary optical polymer including P(St / EMI / MMA) was prepared. The two-dimensional birefringence diagram is a diagram obtained by connecting any two points of the coordinate points of the intrinsic birefringence and photoelastic coefficient of each homopolymer of St, EMI, and MMA with a line in a two-dimensional coordinate axis defined by the intrinsic birefringence and photoelastic coefficient.
[0136] Fig.11It is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / MMA). It should be noted that the unmeasured portion is represented by a dotted line. As described above, in a binary optical polymer containing St, the change in the photoelastic coefficient relative to the composition ratio is nonlinear, so the line segment is also nonlinear. It should be noted that, for example, PSt represents a point representing the characteristics of a homopolymer of St. The same is true for PEMI and PMMA. It should be noted that in the figure, the quadrilateral represents an area very close to the origin.
[0137] By using this two-dimensional birefringence map, an optical polymer having a composition ratio with a small intrinsic birefringence and photoelastic coefficient can be designed, for example, as in the following example. That is, first, the composition ratio of P (St / EMMI) is set so that the coordinate point represented by the photoelastic coefficient and intrinsic birefringence (first photoelastic coefficient and first intrinsic birefringence) determined by the composition ratio of St and the composition ratio of EMI and the coordinate point represented by the photoelastic coefficient and intrinsic birefringence (second photoelastic coefficient and second intrinsic birefringence) of MMA are located at a position sandwiching the origin. Next, the composition ratio of the methacrylic acid derivative is set so that the first photoelastic coefficient and the first intrinsic birefringence are offset by the second photoelastic coefficient and the second intrinsic birefringence.
[0138] Here, the coordinate points represented by the first photoelastic coefficient and the first intrinsic birefringence and the coordinate points represented by the second photoelastic coefficient and the second intrinsic birefringence are arranged with the origin in between, including the case where the three points are arranged on a straight line, but they do not have to be arranged on a straight line, for example, including the case where the straight line connecting the two coordinate points passes through the vicinity of the origin. In addition, the cancellation of the first photoelastic coefficient and the first intrinsic birefringence by the second photoelastic coefficient and the second intrinsic birefringence also includes the case where the sum of the second photoelastic coefficient and the first photoelastic coefficient is zero, and the sum of the second intrinsic birefringence and the first photoelastic coefficient is zero, but also includes the case where the sum of at least one of the two is close to zero. In this way, the absolute value of the photoelastic coefficient can be 50×10 -12 Pa -1 The absolute value of intrinsic birefringence is 20×10 -3 The following optical polymer materials.
[0139] (Production of ternary optical polymers)
[0140] use Fig.11 The two-dimensional birefringence diagram of P (St / EMI / MMA) was obtained by setting the monomer amounts and composition ratios shown in Table 5 to produce a ternary optical polymer film. St (wt.%), EMI (wt.%), and MMA (wt.%) are the mass ratios when the materials are charged.
[0141]
Table 5
[0142] (Table 5)
[0143] monomer St EMI MMA Feeding amount 0.85g 3.15g 1g Feed composition ratio 17wt.%(18.8mol.%) 63wt.%(58.1mol.%) 20wt.%(23.1mol.%)
[0144] Specifically, the monomers shown in Table 5 are prepared and polymerized by the same process as in the case of the alternating copolymer but with the conditions appropriately optimized. The block obtained by cutting off both ends of the cylindrical block of the optical polymer material produced by this process is further purified by the same process as in the case of the alternating copolymer but with the conditions appropriately optimized. For example, reduced pressure drying in a reduced pressure dryer is performed at 90° C. for 24 hours.
[0145] The glass transition temperature of the purified polymer obtained through the above process was measured using DSC-60 (DSC).
[0146] Furthermore, the purified polymer is formed into a thin film by the same process as in the case of the alternating copolymer but with the conditions appropriately optimized.
[0147] The photoelastic coefficient of the produced polymer film was measured using ABR-EX.
[0148] Next, the polymer film was subjected to uniaxial heat stretching using the IMC-11A9 biaxial stretching device of the Well Moto Seisakusho. Then, the internal stress was relaxed by standing for more than 24 hours, and the orientation of the stretched film was evaluated using infrared dichroism based on the absorbance in the infrared region of Varian 7000e. In addition, the retardation of the stretched film was measured using ABR-10A. Then, the intrinsic birefringence was calculated based on the retardation, orientation and thickness of the film. In addition, the refractive index of a portion of the polymer film was measured to infer the copolymer composition ratio.
[0149] An example of the properties of the produced optical polymer material and optical film is shown in Table 6. As shown in Table 6, when St is 17wt.%, EMI is 63wt.%, and MMA is 20wt.%, a high glass transition temperature of 156°C can be obtained, confirming high heat resistance. It should be noted that the optical polymer material and the optical film are modified in such a way that their glass transition temperature is lower than 193.9°C in the case of the binary system without MMA shown in Table 2. Such a temperature of 156°C is higher than the glass transition temperature of acrylic resin and is equivalent to the glass transition temperature of polycarbonate, which is 150°C. Therefore, it can be said that the optical polymer material and the optical film have high heat resistance and are easy to injection mold. In addition, the inherent birefringence Δn 0 0.10×10 at 25°C -3 , temperature coefficient dΔn 0 / dT is 1.21×10 -5 ℃ -1, the photoelastic coefficient C is -0.24×10 -12 Pa -1 , are all extremely low values close to zero, confirming good low birefringence characteristics.
[0150]
Table 6
[0151] (Table 6)
[0152] <![CDATA[Δn 0 (×10 -3 )]]> <![CDATA[C(×10 -12 Well -1 )]]> <![CDATA[dΔn 0 / dT(×10 -5 ℃ -1 )]]> <![CDATA[T g (℃)]]> 0.10 -0.24 1.21 156
[0153] Furthermore, a two-dimensional birefringence graph of P(St / CHMI / MMA), which is a ternary optical polymer using N-cyclohexylmaleimide (CHMI) as a maleimide derivative, was prepared.
[0154] Fig.12 2 is a diagram showing a two-dimensional birefringence diagram of P(St / CHMI / MMA). It should be noted that the unmeasured portion is indicated by a dotted line. In addition, in the figure, the quadrilateral represents an area very close to the origin. Fig.11 Similarly, in a binary optical polymer containing St, the photoelastic coefficient changes nonlinearly with respect to the composition ratio, and therefore the line segment also has a nonlinear shape.
[0155] By using this two-dimensional birefringence diagram, an optical polymer with a composition ratio having a small intrinsic birefringence and photoelastic coefficient can be designed, for example, as in the following example. That is, first, the composition ratio of P (St / CHMI) is set so that the coordinate point represented by the photoelastic coefficient and intrinsic birefringence (the first photoelastic coefficient and the first intrinsic birefringence) determined by the composition ratio of St and the composition ratio of CHMI and the coordinate point represented by the photoelastic coefficient and intrinsic birefringence (the second photoelastic coefficient and the second intrinsic birefringence) of MMA are located at a position sandwiching the origin. Next, the composition ratio of the methacrylic acid derivative is set in such a way that the first photoelastic coefficient and the first intrinsic birefringence are offset by the second photoelastic coefficient and the second intrinsic birefringence. In this way, an absolute value of the photoelastic coefficient of 50×10 -12 Pa -1 The absolute value of intrinsic birefringence is 20×10 -3 The following optical polymer materials.
[0156] use Fig.12 The two-dimensional birefringence diagram of P (St / CHMI / MMA) was obtained by setting the monomer amounts and composition ratios shown in Table 7 to produce a ternary optical polymer film. St (wt.%), CHMI (wt.%), and MMA (wt.%) are the mass ratios when the materials are charged.
[0157]
Table 7
[0158] (Table 7)
[0159] monomer St CHMI MMA Feeding amount 0.30g 2.00g 2.70g Feed composition ratio 6wt.%(7mol.%) 40wt.%(27.2mol.%) 54wt.%(65.8mol.%)
[0160] Specifically, the monomers shown in Table 7 were prepared and polymerized by the same process as in the case of P(St / EMI / MMA) but with the conditions appropriately optimized. The block obtained by cutting off both ends of the cylindrical block of the optical polymer material prepared by this process was further purified by the same process as in the case of P(St / EMI / MMA) but with the conditions appropriately optimized.
[0161] The glass transition temperature of the purified polymer obtained through the above process was measured using DSC-60 (DSC).
[0162] Furthermore, the purified polymer is formed into a thin film by the same process as in the case of P(St / EMI / MMA) but with the conditions appropriately optimized.
[0163] The photoelastic coefficient of the produced polymer film was measured using ABR-EX.
[0164] Next, the polymer film was subjected to uniaxial heat stretching using IMC-11A9. Then, the internal stress was relaxed by standing for more than 24 hours, and the orientation of the stretched film was evaluated using infrared dichroism based on the absorbance in the infrared region using Varian 7000e. In addition, the retardation of the stretched film was measured using ABR-10A. Then, the intrinsic birefringence was calculated from the retardation, orientation and film thickness. In addition, the refractive index of a portion of the polymer film was measured to infer the copolymer composition ratio.
[0165] An example of the properties of the produced optical polymer material and optical film is shown in Table 8. As shown in Table 8, it was confirmed that when St was 6 wt.%, CHMI was 40 wt.%, and MMA was 54 wt.%, a high glass transition temperature of 161°C was obtained, and the heat resistance was high and injection molding was easy. In addition, the intrinsic birefringence Δn 0 At 25°C, it is -5.23×10 -3 , the photoelastic coefficient C is -0.12×10 -12 Pa -1 , are all extremely low values close to zero, confirming good low birefringence characteristics.
[0166]
Table 8
[0167] (Table 8)
[0168] <![CDATA[Δn 0 (×10 -3 )]]> <![CDATA[C(×10 -12 Well -1 )]]> Tg -5.23 -0.12 161
[0169] Furthermore, a two-dimensional birefringence graph of P(St / EMI / TCEMA), a ternary optical polymer using TCEMA (2,2,2-trichloroethyl methacrylate), a methacrylic acid derivative, as a modified organic compound, was prepared.
[0170] Fig.13 This is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / TCEMA). It should be noted that the unmeasured portion is indicated by a dotted line. In addition, in the figure, the quadrilateral represents the area very close to the origin. Using this two-dimensional birefringence diagram, it is possible to achieve an absolute value of the photoelastic coefficient of 50×10 -12 Pa -1 The absolute value of intrinsic birefringence is 20×10 -3 The following optical polymer materials.
[0171] use Fig.13 The two-dimensional birefringence diagram of P (St / EMI / TCEMA) was obtained by setting the monomer amounts and composition ratios shown in Table 9 to produce a ternary optical polymer film. St (wt.%), EMI (wt.%), and TCEMA (wt.%) are the mass ratios when the materials are charged.
[0172]
Table 9
[0173] (Table 9)
[0174] monomer St EMI TCEMA Feeding amount 1.15g 3.45g 0.4g Feed composition ratio 23.0wt.%(27.3mol.%) 69.0wt.%(68.2mol.%) 8.0wt.%(4.5mol.%)
[0175] An example of the properties of the produced optical polymer material and optical film is shown in Table 10. As shown in Table 10, it was confirmed that when St was 23 wt.%, EMI was 69 wt.%, and TCEMA was 8 wt.%, a high glass transition temperature of 188°C was obtained, indicating high heat resistance. 0 At 25°C, it is -0.65×10 -3 , the photoelastic coefficient C is 0.08×10 -12 Pa -1 , are all extremely low values close to zero, confirming good low birefringence characteristics.
[0176]
Table 10
[0177] (Table 10)
[0178] <![CDATA[Δn 0 (×10 -3 )]]> <![CDATA[C(×10 -12 Well -1 )]]> <![CDATA[T g (℃)]]> -0.65 0.08 188
[0179] Furthermore, a two-dimensional birefringence map of P(St / EMI / tBuMI) using tBuMI as a maleimide derivative of a modified organic compound was prepared as a ternary optical polymer.
[0180] Fig.14 : This is a diagram showing a two-dimensional birefringence diagram of P(St / EMI / tBuMI). It should be noted that the unmeasured portion is indicated by a dotted line. In addition, in the figure, the quadrilateral represents the area very close to the origin. The intrinsic birefringence of tBuMI is positive. Using this two-dimensional birefringence diagram, it is possible to achieve an absolute value of the photoelastic coefficient of 50×10 -12 Pa -1 The absolute value of intrinsic birefringence is 20×10 -3 The following optical polymer materials.
[0181] use Fig.14 The two-dimensional birefringence diagram of P (St / EMI / tBuMI) was obtained by setting the monomer amounts and composition ratios shown in Table 11 to produce a ternary optical polymer film. St (wt.%), EMI (wt.%), and tBuMI (wt.%) are the mass ratios when the materials are added.
[0182]
Table 11
[0183] (Table 11)
[0184] monomer St EMI ikB Feeding amount 1.00g 2.50g 0.50g Feed composition ratio 25.0wt.%(29mol.%) 62.5wt.%(61mol.%) 12.5wt.%(10mol.%)
[0185] An example of the properties of the produced optical polymer material and optical film is shown in Table 12. As shown in Table 12, it was confirmed that when St was 25.0 wt.%, EMI was 62.5 wt.%, and tBuMI was 12.5 wt.%, a glass transition temperature higher than P (St / EMI) of 197°C was obtained, indicating high heat resistance. 0 3.68×10 at 25°C -3 , the photoelastic coefficient C is 0.27×10 -12 Pa -1 , are all extremely low values close to zero, confirming good low birefringence characteristics.
[0186]
Table 12
[0187] (Table 12)
[0188] <![CDATA[Δn 0 (×10 -3 )]]> <![CDATA[C(×10 -12 Well -1 )]]> <![CDATA[T g (℃)]]> 3.68 0.27 197
[0189] As shown in the example of P(St / EMI / tBuMI), the modified organic compound is not limited to methacrylic acid derivatives, and the sign of its photoelastic coefficient can be either positive or negative. In addition, in the modified organic compound, the physical property value different from the monomer of the styrene derivative and the monomer of the maleimide derivative is not limited to the glass transition temperature, but can also be other physical property values related to mechanical strength. In this way, an optical polymer material with more preferred physical property values related to mechanical strength can be obtained. In addition, the modified organic compound can contain two or more different monomers.
[0190] In addition, the embodiment is not limited to the embodiment. The scheme formed by appropriately combining the constituent elements is also included in the present invention. In addition, those skilled in the art can easily derive further effects and variations. Therefore, the broader aspects of the present invention are not limited to the embodiment, and various changes can be made.
[0191] Description of Reference Numerals
[0192] 10: Liquid crystal display device
[0193] 1: Backlight
[0194] 2.9: Polarizing plate
[0195] 3.8: Retardation Film
[0196] 4, 6: Glass substrate with transparent electrode
[0197] 5: Liquid crystal layer
[0198] 7: RGB color filter
Claims
1. An optical polymer material, characterized in that: A polymer composed of a monomer of a styrene derivative, a monomer of a maleimide derivative and a monomer of a modified organic compound, wherein the monomer of the modified organic compound has a physical property value related to mechanical strength different from the monomer of the styrene derivative and the monomer of the maleimide derivative, In the relationship between the monomer of the styrene derivative and the monomer of the maleimide derivative, the photoelastic coefficient has a nonlinear characteristic that the photoelastic coefficient decreases to a second value as the composition ratio of the styrene derivative increases, and increases from the second value if the composition ratio of the styrene derivative further increases. The styrene derivative has a predetermined composition ratio, an absolute value of a photoelastic coefficient of which is less than or equal to a third absolute value, and an absolute value of a specific birefringence of which is less than or equal to a fourth absolute value. In the two-dimensional birefringence diagram defined by the intrinsic birefringence and the photoelastic coefficient, The composition ratio of the styrene derivative and the composition ratio of the maleimide derivative are set in such a manner that the coordinate points indicated by the first photoelastic coefficient and the first intrinsic birefringence determined by the composition ratio of the styrene derivative and the composition ratio of the maleimide derivative and the coordinate points indicated by the second photoelastic coefficient and the second intrinsic birefringence of the modified organic compound are located at positions sandwiching an origin, and the composition ratio of the modified organic compound is set in such a manner that the first photoelastic coefficient and the first intrinsic birefringence are offset by the second photoelastic coefficient and the second intrinsic birefringence.
2. The optical polymer material according to claim 1, characterized in that A homopolymer comprising the maleimide derivative.
3. An optical polymer material, characterized in that: A polymer composed of a monomer of a styrene derivative, a monomer of a maleimide derivative and a monomer of a modified organic compound, wherein the monomer of the modified organic compound has a physical property value related to mechanical strength different from the monomer of the styrene derivative and the monomer of the maleimide derivative, In the relationship between the monomer of the styrene derivative and the monomer of the maleimide derivative, the photoelastic coefficient has a nonlinear characteristic that the photoelastic coefficient decreases to a second value as the composition ratio of the styrene derivative increases, and increases from the second value if the composition ratio of the styrene derivative further increases. The styrene derivative has a predetermined composition ratio, an absolute value of a photoelastic coefficient of which is less than or equal to a third absolute value, and an absolute value of a specific birefringence of which is less than or equal to a fourth absolute value. The optical polymer material comprises a homopolymer of the maleimide derivative.
4. The optical polymer material according to claim 1 or 3, characterized in that: The third absolute value is 50×10 - 12 Pa -1 , the fourth absolute value is 20×10 -3 .
5. The optical polymer material according to claim 1 or 3, characterized in that: The glass transition temperature is higher than that of the acrylic resin and lower than that of the case where the modified organic compound is not contained, or the glass transition temperature is higher than that of the case where the modified organic compound is not contained.
6. The optical polymer material according to claim 1 or 3, characterized in that: The styrene derivative is styrene, the maleimide derivative is ethylmaleimide or cyclohexylmaleimide, and the modified organic compound is a methacrylic acid derivative or tert-butylmaleimide.
7. The optical polymer material according to claim 6, characterized in that The composition ratio of the styrene derivative is in the range of 6%, 17%, 23% or 25% in terms of mass ratio, and in the range of 7%, 18.8%, 27.3% or 29% in terms of molar ratio.
8. The optical polymer material according to claim 1 or 3, characterized in that: The maleimide derivative is contained in an amount greater than that of the styrene derivative.
9. An optical film, characterized in that: Comprising the optical polymer material according to claim 1 or 3.
10. A display device, characterized in that: A method of manufacturing the optical film according to claim 9.
11. A method for producing an optical polymer material, characterized in that: The method comprises the steps of forming an optical polymer material, wherein the optical polymer material comprises a polymer formed of a monomer of a styrene derivative, a monomer of a maleimide derivative and a monomer of a modified organic compound, wherein the modified organic compound has a physical property value related to mechanical strength different from that of the monomer of the styrene derivative and the monomer of the maleimide derivative, The styrene derivative is within a specified composition ratio range. The optical polymer material is formed such that the absolute value of the photoelastic coefficient is less than or equal to the third absolute value and the absolute value of the intrinsic birefringence is less than or equal to the fourth absolute value within the range of the composition ratio. In the two-dimensional birefringence diagram defined by the intrinsic birefringence and the photoelastic coefficient, The composition ratio of the styrene derivative and the composition ratio of the maleimide derivative are set so that the coordinate point represented by the first photoelastic coefficient and the first intrinsic birefringence determined by the composition ratio of the styrene derivative and the composition ratio of the maleimide derivative and the coordinate point represented by the second photoelastic coefficient and the second intrinsic birefringence of the modified organic compound are located at a position sandwiching the origin, The composition ratio of the modified organic compound is set so as to cancel out the first photoelastic coefficient and the first intrinsic birefringence.
12. A method for producing an optical polymer material, characterized in that: The method comprises the steps of forming an optical polymer material, wherein the optical polymer material comprises a polymer formed of a monomer of a styrene derivative, a monomer of a maleimide derivative and a monomer of a modified organic compound, wherein the modified organic compound has a physical property value related to mechanical strength different from that of the monomer of the styrene derivative and the monomer of the maleimide derivative, The styrene derivative is within a specified composition ratio range. The optical polymer material is formed such that the absolute value of the photoelastic coefficient is less than or equal to the third absolute value and the absolute value of the intrinsic birefringence is less than or equal to the fourth absolute value within the range of the composition ratio. The optical polymer material comprises a homopolymer of the maleimide derivative.
13. The method for producing an optical polymer material according to claim 11 or 12, characterized in that: The polymer is formed by blending a material that becomes a maleimide derivative in a larger amount than a material that becomes a styrene derivative.
14. The method for producing an optical polymer material according to claim 11 or 12, characterized in that: The third absolute value is 50×10 -12 Pa -1 , the fourth absolute value is 20×10 -3 .
15. A method for manufacturing an optical film, characterized in that: The optical polymer material produced by the method for producing an optical polymer material according to claim 11 or 12 is formed into an optical film.
Citation Information
Patent Citations
Resin composition and optical molded article
JP2008094912A
Optical element, polarizer, retardation plate, illuminator, and liquid crystal display
JP2008242349A
Acrylic resin-containing film, and polarizing plate and display device produced by using the same
JP2009179731A
Film, method of manufacturing the same, polarizing plate, and liquid crystal display device
JP2011048025A
Retardation film
JP2015197483A